Compact Spectrometer: A Dedicated Compact Wide Band Spectrometer for Free-Electron Laser Monitoring - Gabriele Zeni; Fabio Frassetto; Michele Di Fraia; Marcello Coreno; Giuseppe Sansone; Adriano Contillo; Carlo Callegari; Luca Poletto (Photonics)
The calibration activities of the COmpact SPectrometer—COSP for the FERMI Free-Electron Laser (FEL) facility at the Elettra Synchrotron (Italy) are presented. COSP is an in-house built grating spectrometer designed to be used during the optimization of the FERMI parameters and to control the relative stability between different FEL harmonics in the multi-harmonic emission mode. The spectrometer is designed to work in single-shot mode at a repetition rate of 50 Hz providing medium resolution in a wide spectral range in order to either measure the separate intensities of the harmonics being mixed in a multi-color experiment or to quantify the amount of possible spurious harmonics. These activities are of key importance in the new class of experiments based on the wave mixing paradigm tested at the seeded FEL FERMI.